Impaired Neuronal Differentiation of Neural Stem Cells Lacking the Engrailed-2 Gene. (21st August 2018) - Boschian, Camilla; Messina, Andrea; Bozza, Angela; Castellini, Maria Elena; Provenzano, Giovanni; Bozzi, Yuri; Casarosa, Simona
Highlights: Neural stem cells (NSCs) from mouse basal ganglia and neocortex express En2. Basal ganglia-derived En2 −/− NSCs show impaired GABAergic differentiation. Basal ganglia-derived En2 −/− NSCs express low levels of the BDNF receptor trkB. Neocortex-derived En2 −/− NSCs express trkB and differentiate into neurons. En2 contributes to GABAergic neuron differentiation via BDNF signaling. Abstract: The Engrailed-2 ( En2 ) gene codes for a homeobox-containing transcription factor, involved in midbrain-hindbrain embryonic development. In postnatal brain, En2 is expressed in the ventral mesencephalon, cerebellum, hippocampus and neocortex. Two single-nucleotide polymorphisms (SNPs) that are associated to autism spectrum disorders (ASD) have been identified in the human EN2 gene. Accordingly, mice lacking the En2 homeodomain ( En2 hd/hd, referred to as En2 −/− ) show molecular, anatomical and behavioral "ASD-like" features. Among these, we previously showed a partial loss of GABAergic interneurons in the En2 −/− postnatal hippocampus and neocortex, accompanied by a marked decrease of brain-derived neurotrophic factor (BDNF) signaling, a crucial determinant of GABAergic differentiation. In order to better investigate the role of En2 in GABAergic interneuron differentiation, we generated and subsequently differentiated neural stem cells (NSCs) from basal ganglia and neocortex of En2 +/+ and En2 −/− mouse embryos. Wild-type NSCs from both basal ganglia and neocortex express En2, while mutant ones do not, as expected. As compared to En2 +/+ NSCs, En2 −/− NSCs derived from basal ganglia show impaired GABAergic differentiation accompanied by a reduced expression of the BDNF receptor trkB. Conversely, En2 −/− NSCs derived from the neocortex expressed high levels of trkB and readily differentiated into neurons, as En2 +/+ NSCs. Our results suggest that En2 contributes to GABAergic neuron differentiation from basal ganglia NSCs through a trkB-dependent BDNF signaling, thus providing a possible explanation for the reduced number of GABAergic interneurons detected in the En2 −/− postnatal forebrain.